1997
DOI: 10.1111/j.1749-6632.1997.tb51749.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nitric Oxide in the Pathophysiology of Acute Heat Stress in the Rat

Abstract: The possibility that nitric oxide (NO) is involved in the pathophysiology of brain injury caused by heat stress (HS) was examined using immunohistochemistry of a constitutive isoform of neuronal nitric oxide synthase (c-NOS) in a rat model. In addition, to discover the role of oxidative stress in inducing c-NOS activity in HS, the effect of a new antioxidant H-290/51 on HS-induced expression of c-NOS immunoreactivity was examined. Subjection of conscious young animals to a 4-h HS in a biological oxygen demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 36 publications
(68 reference statements)
1
25
0
1
Order By: Relevance
“…Intestinal mucosal permeability to endotoxin increases during heatstroke in the rat (26); this alteration enhances production of cytokines that induce nitric oxide (NO) overproduction in the rat (27). Indeed, plasma or cerebral levels of NO are elevated in heatstroke rats (27,28; present results).…”
Section: Stress Accordingly Cd34supporting
confidence: 52%
See 1 more Smart Citation
“…Intestinal mucosal permeability to endotoxin increases during heatstroke in the rat (26); this alteration enhances production of cytokines that induce nitric oxide (NO) overproduction in the rat (27). Indeed, plasma or cerebral levels of NO are elevated in heatstroke rats (27,28; present results).…”
Section: Stress Accordingly Cd34supporting
confidence: 52%
“…Indeed, plasma or cerebral levels of NO are elevated in heatstroke rats (27,28; present results). Aminoguanidine, an inducible nitric oxide synthase (iNOS) inhibitor, improves heat tolerance in the rat by preserving the splanchnic blood flow (29) and reducing intracranial hypertension and cerebral ischemia and damage (30).…”
Section: Stress Accordingly Cd34mentioning
confidence: 81%
“…nNOS mRNA expression is tightly regulated, consistent with its role in development (28) and in the adaptation to environmental stress (45,46). This level of fine control is imposed, in part, through the cell-and tissue-specific production of different RNA transcripts (47).…”
Section: Figurementioning
confidence: 82%
“…Both pyrogenic cytokines and endothelium-derived factors can interfere with normal thermoregulation, thereby precipitating arterial hypotension, hyperthermia, and heatstroke (4). Plasma or brain nitrite / nitrate levels are elevated in heatstroke patients (5) and rats (6,7). A more recent report has also shown that aminoguanidine (AG) slows the rate of NO production, preserves the splanchnic blood flow, and improves heat tolerance in rats (2).…”
Section: Introductionmentioning
confidence: 93%